2020
DOI: 10.1021/acsaelm.9b00779
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Flexible Organic Field-Effect Transistors with Barium Strontium Titanate Gate Dielectric Deposited at Room Temperature

Abstract: Reducing the operating voltage and processing temperature are the crucial factors in the progression of organic field-effect transistors (OFETs) in flexible portable applications. Here, we have demonstrated RF sputtering deposited Ba 0.5 Sr 0.5 TiO 3 (BST) as high-k dielectric material for high performance operationally stable flexible low voltage operated OFETs. It was found that the BST deposition parameters can enormously affect the film properties like dielectric constant, surface morphology, and the cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Most recently, a stunning 7-order of magnitude enhancement in conductivity was reported for bent coronene crystals, a result in sharp contrast with the more modest changes described above. The frequency of contributions on the electromechanical analysis of organic semiconductors indicates that this is an inquiry likely to develop quickly in the near term, and may come into focus in tandem with the development of the basic science of mechanically dynamic molecular crystals. …”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a stunning 7-order of magnitude enhancement in conductivity was reported for bent coronene crystals, a result in sharp contrast with the more modest changes described above. The frequency of contributions on the electromechanical analysis of organic semiconductors indicates that this is an inquiry likely to develop quickly in the near term, and may come into focus in tandem with the development of the basic science of mechanically dynamic molecular crystals. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the preparation of nanofillers/polymer composites has become an effective way to further improve the dielectric properties . At present, the commonly used ceramic fillers include barium titanate (BT), titanium dioxide (TiO 2 ), and barium strontium titanate. , In addition, these ceramic nanoparticles can be transformed into one-dimensional nanowires or two-dimensional nanosheets to further improve the dielectric properties of the ceramic-filled composites. , Many studies have shown that one-dimensional ceramic fillers with high aspect ratios have greater advantages than spherical ceramic fillers in enhancing the dielectric constant of composites with low filler addition. However, regardless of what dimension of ceramic nanofillers is used, the dielectric constant of composites can be improved only when the high ceramic filling amount is greater than 50%, which often leads to the destruction of mechanical properties of composites.…”
Section: Introductionmentioning
confidence: 99%
“…[9,13] Naturally, altering intermolecular interactions and vibrational frequencies can influence electronics but teasing apart the static and dynamic influences on charge mobilities will require more collective attention as electromechanical analyses of organic semiconductors appear with increasing frequency. [13,14] A unified understanding may come into focus in tandem with the basic science of mechanically dynamic molecular crystals. [15][16][17][18] Electromechanical effects of twisting have yet to be examined.…”
Section: Introductionmentioning
confidence: 99%